1984
DOI: 10.1002/ar.1092100414
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural characterization of glial cells in the rat pineal gland with special reference to the pineal stalk

Abstract: In the present study the "interstitial" cells of the superficial pineal gland and the nonparenchymal cells of the pineal stalk in Sprague-Dawley rats were examined ultrastructurally with the aim of defining the cells more closely. The "interstitial" cells of the superficial pineal gland do not represent a homogeneous cell population. The most abundant cell type is the mononuclear phagocyte, most easily recognized by its dark appearance and its content of primary and conspicuous secondary lysosomes. Astrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
3

Year Published

1988
1988
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
(35 reference statements)
2
20
0
3
Order By: Relevance
“…Electron microscopic observations on the pineal gland of the rat (Luo et al, 1984) and guinea pig have shown that myelinated and unmyelinated fibers from the habenular and posterior commissures enter the proximal portion of the gland and that these fibers reach the distal portion through the intermediate portion in the rat. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopic observations on the pineal gland of the rat (Luo et al, 1984) and guinea pig have shown that myelinated and unmyelinated fibers from the habenular and posterior commissures enter the proximal portion of the gland and that these fibers reach the distal portion through the intermediate portion in the rat. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Bu hücreler ışık mikroskobunda pinealositlere göre daha kü-çük ve koyu boyanan çekirdekleriyle ayırdolunurlar (7,16,24). Bu hüc-reler daha çok astrositlere benzetilmektedir (17,18,22,24). Bazı araştır-macılar fibröz astrositler olduklarını iddia etmektedirler (13,16).…”
Section: Discussionunclassified
“…Bu hücreler dışında bağ dokusu bölmelerine bağlı olarak organ, içinde bağ dokusu hücreleri de gözlenmektedir (13,17,23). Bu araştırma-da da bağ dokusu bölmelerinde bağ dokusu hücreleri, özellikle insanda daha fazla olarak görüldü.…”
Section: Discussionunclassified
“…This agrees with the heterogeneity of pinealocytes reported by other investigators. Evidence for such morphological heterogeneity was seen in the staining properties of pineal parenchyma1 cells (Tapp and Blumfield, 1970) and in the varying electron densities of light and dark pinealocytes (Arstila, 1967;Benson and Satterfield, 1975;Luo et al, 1984). Based on ultrastructural variations (Pevet, 1977;Pevet and Kuyper, 1978) and a possible link to photoreceptor cells (Pevet et al, 19771, two mammalian pinealocyte populations (I and 11) were identified.…”
Section: Discussionmentioning
confidence: 99%